The Importance of Education and Knowledge of Prospective Parents in Preventing Stunting - Hasmi Hakim; Sri Wahyuni; Erwing (Bulletin of Science Education, 2024)
Prospective parents have very minimal knowledge about the importance of nutrition for children. This research aims to explore the importance of education and knowledge of prospective parents in preventing stunting in children. This research approach is qualitative with a case study research design. Data collection was obtained through in-depth interviews, participatory exploration and group discussions. The research results show that prospective parents who have a good understanding of nutrition and health tend to be better able to provide appropriate nutritional intake for their children. A higher educational background also contributes to awareness and responsiveness to children's nutritional needs. However, there are significant obstacles such as limited access to information, low levels of formal education, and the influence of local culture that does not support the practice of providing nutritious food. This research recommends improving community-based health education programs for expectant parents, including providing materials that are easier to understand and relevant to the local context.